A Multifunctional Flexible Composite Film with Excellent Multi‐Source Driven Thermal Management, Electromagnetic Interference Shielding, and Fire Safety Performance, Inspired by a "Brick–Mortar" Sandwich Structure. (29th March 2022) - Gong, Shang; Sheng, Xinxin; Li, Xiaolong; Sheng, Mengjie; Wu, Hao; Lu, Xiang; Qu, Jinping
Abstract: The rapid development of portable flexible electronic devices means a multifunctional composite film with excellent thermal management capability, high electromagnetic interference (EMI) shielding, and a strong fire safety performance is urgently required. In this paper, inspired by a "brick–mortar" sandwich structure, phase change capsules (PCCs) and MXene nanosheets are prepared. Subsequently, a one‐step vacuum‐assisted filtration method is used to fabricate a multifunctional flexible PCC/MXene/polyvinyl alcohol (PMP) phase change composite film with high light‐to‐thermal conversion efficiency, Joule heating generation, fire safety, and EMI shielding effects. The superior preparation technology endows the film with multi‐source driven thermal management capabilities and excellent EMI shielding effectiveness values (43.13 dB). In addition, the PMP film exhibits good flexibility and high enthalpy (136.8 J g −1 ). Surprisingly, the PMP film's excellent fire safety properties improve its reliability and safety. In summary, the simple preparation technique and outstanding overall performance of the PMP films provide broad application prospects in advanced thermal management and EMI shielding in wearable products. Abstract : An integrated multifunctional flexible phase‐change capsules/MXene/polyvinyl alcohol phase change composite film featuring high light‐to‐thermal conversion efficiency, Joule heating generation, fire safety, and electromagnetic interference (EMI) shielding effects is prepared by a simple vacuum‐assisted filtration technology. The composite film demonstrates multi‐source driven thermal management capabilities, good EMI shielding performance (43.13 dB), optional flexibility, and high enthalpy (136.8 J g −1 ).